Exploring Botanical Innovations in Fish Aquaculture: A Review of Biological Impacts and Industry Prospects: Exploring Botanical Innovations in Fish Aquaculture - Cherukumudi, Krishnaveni; Augustian, Hridya T.; Kausar, Nahid; Biju, Jyothika; Rao, Keerthi G.; Gopalraaj, Jhanani; Velayudhannair, Krishnakumar; Kandathil Radhakrishnan, Divya; Tomson, Majesh (Fishery Technology, 2024)
Culture fisheries play a crucial role in providing protein-rich sustenance for the expanding global population. However, the intensification of fish farming comes with a downside – heightened stress among fish, which subsequently escalates the risk of disease transmission. The emergence of resilient bacterial populations and the accumulation of residues in body tissues due to the use of drugs and chemicals have underscored the necessity for the development of environmentally friendly and durable solutions. Notably, there has been a recent upsurge in interest regarding the use of botanical products to enhance aquaculture practices. Plant derived secondary metabolites have demonstrated their efficacy in stimulating appetite, facilitating growth, boosting immune responses, and exhibiting antibacterial as well as anti-parasitic properties within the realm of aquaculture. This article aims to comprehensively examine the body of research on the application of plant-derived products in pisciculture, elucidating their effects on various biological aspects of fish, including growth patterns, immune system functionality, pigmentation, blood composition, and reproductive parameters. Furthermore, the article also delivers inputs into an assessment of the current status of these practices, the methodologies deployed, and the challenges encountered in integrating plant-based solutions into the aquaculture industry.